PREDICTORS OF THE FUNCTIONAL REACH TEST IN PEOPLE WITH PARKINSON'S DISEASE - Morais, Luana Carolina De; Pereira, Marcelo Pinto; Lahr, Juliana; Pelicioni, Paulo Henrique Silva; Rinaldi, Natália Madalena; Gobbi, Lilian Teresa Bucken (Universidade Estadual de Maringá, 2017)
ABSTRACT Postural instability, a fundamental signal/symptom of Parkinson’s disease (PD), is characterized by the association between postural alignment, joint range of motion, and muscular rigidity. The aim of the present study was to analyze the relationship between performance in the functional reach test (FRT) and associated factors such as joint range of motion and PD clinical features. Twenty-five people with PD in stages 1 and 1.5 of the Hoehn & Yahr scale participated in the study. The analyzed dependent variables were: FRT performance and scores in the items of clinical evaluation of the Unified Parkinson’s Disease Rating Scale: pull-test, motor rigidity, and motor condition were used. The average distance in the FRT was 25.3 cm and the mean anterior-posterior displacement of the center of pressure was 2.69 cm. The ankle range of motion was associated with FRT performance, while postural stability was associated with the anterior-posterior displacement of the center of pressure during the FRT. We conclude that FRT performance in people with PD is determined by the individual level of balance and by the ankle joint amplitude and muscular rigidity and functional alterations due to aging are responsible for FRT performance.

RESUMO A instabilidade postural, um sinal/sintoma cardinal da doença de Parkinson (DP), é caracterizada pela associação entre alinhamento postural, amplitude de movimento e rigidez muscular. O objetivo foi analisar a relação entre o desempenho no teste de alcance funcional (TAF) e fatores relacionados a amplitude de movimento e aspectos clínicos da doença. Participaram 25 pessoas com DP nos estágios 1,0 e 1,5 da Hoehn e Yahr. As variáveis dependentes analisadas foram: desempenho no TAF e as pontuações nos itens da avaliação clínica da UnifiedParkinson’sDisease Rating Scale: teste de retropulsão, rigidez muscular e condição motora. A distância média no TAF foi de 25,3 cm e o deslocamento anteroposterior médio do centro de pressão foi de 2,69 cm. A amplitude de movimento articular do tornozelo está associada ao desempenho no TAF, enquanto a estabilidade postural está associada ao deslocamento anteroposterior do centro de pressão durante o TAF. Conclui-se que o desempenho no TAF em pessoas com DP é determinado pelo nível individual de equilíbrio e pela amplitude articular do tornozelo e a rigidez muscular e alterações funcionais do envelhecimento são responsáveis pelo desempenho no TAF.
PREDITORES DO DESEMPENHO NO TESTE DE ALCANCE FUNCIONAL EM PESSOAS COM DOENÇA DE PARKINSON
Keywords: Postural balance; Parkinson’s disease; Muscular rigidity.; Equilíbrio postural; Doença de Parkinson; Rigidez muscular.